HBc: the multifunctional architect of HBV replication, immune evasion, and therapeutic innovation - Zhu, Yujia; Song, Hongxiao; Xu, Fengchao; Huang, Mian; Tan, Guangyun (Frontiers in Immunology, 2025)
The hepatitis B core protein (HBc) is a multifunctional viral protein central to hepatitis B virus (HBV) replication, immune modulation, and capsid assembly. Structurally, HBc consists of an N-terminal domain (NTD) essential for capsid formation and a C-terminal domain (CTD) critical for RNA binding and genome packaging. Frequent HBc mutations, driven by HBV’s high mutation rate, enhance the virus’s ability to adapt to environmental pressures. HBc interacts with host factors to regulate viral transcription, stabilize capsids, and modulate immune responses, including the suppression of interferon signaling and promotion of immune exhaustion. Clinically, anti-HBc antibodies serve as key diagnostic markers, while HBc-targeting therapies, such as capsid assembly modulators (CAMs), represent promising strategies for achieving functional cure. This review uniquely integrates structural, functional, and clinical perspectives on HBc, providing a comprehensive understanding of its role in HBV biology and its potential as a therapeutic target. By highlighting recent advances in CAMs and the challenges of drug resistance, this work offers valuable insights for researchers and clinicians aiming to develop innovative HBV treatments.